The expression of CYP2W1 in colorectal primary tumors, corresponding lymph node metastases and liver metastases. (July 2014) - Stenstedt, Kristina; Hallstrom, Marja; Lédel, Frida; Ragnhammar, Peter; Ingelman-Sundberg, Magnus; Johansson, Inger; Edler, David
Abstract Introduction. Metastatic disease is a major cause of death in patients with colorectal cancer (CRC). We have previously investigated expression of an orphan cytochrome P450 (CYP) enzyme, CYP2W1, and found high expression in about one third of colorectal tumors. CYP2W1 has proven to metabolize duocarmycin analogs into cytotoxic substances, compounds that in xenografts of CRC cells expressing CYP2W1 completely inhibit tumor growth. This study was designed to evaluate whether the enzyme is expressed in primary CRC and corresponding metastases. Material and methods. Samples from primary tumors, corresponding lymph node metastases and liver metastases from 96 patients were collected and analyzed by immunohistochemistry. Data regarding patient's demographics, tumor characteristics and survival were also collected. Results. Out of 96 patients, 25 (26%) had high CYP2W1 expression in the primary tumor and 46 (48%) showed high levels in the liver metastasis. In total 59 patients had lymph node metastases, and 31% of them had high CYP2W1 expression. When comparing the expression in primary tumor with that of the first liver metastasis, the increase in expression was statistically significant (p = 0.005). Conclusion. High CYP2W1 expression is seen in 26% of primary CRC and in 48% of corresponding liver metastases. This opens possibilities for new targeted therapies to metastatic CRC in the future.